Writing to Cuba : filibustering and Cuban exiles in the United States - Lazo, Rodrigo (University of North Carolina Press, 2005)
A study of the exiled Cuban writers from the 19th century known as los filibusteros who created a body of literature demanding independence from Spain and alliance with or annexation to the US. The transnational culture of writers went hand in hand with economic flow between the countries and was fuelled by belief in a US promise of freedom.
Keywords: Cubans -- United States -- Politics and government -- 19th century.; Authors, Cuban -- Political activity -- United States -- History -- 19th century.; Exiles -- Political activity -- United States -- History -- 19th century.; Filibusters -- Cuba -- History -- 19th century.; United States -- Relations -- Cuba.; Cuba -- Relations -- United States.; Cuba -- History -- 1810-1899.; Cubans -- United States -- Intellectual life -- 19th century.; Cuban newspapers -- United States -- History -- 19th century.; Écrivains cubains -- Activité politique -- États-Unis -- Histoire -- 19e siècle.; Flibustiers -- Cuba -- Histoire -- 19e siècle.; Cuba -- Relations -- États-Unis.; Cuba -- Histoire -- 1810-1899.; LITERARY CRITICISM -- European -- Spanish & Portuguese.; Cuban newspapers; Cubans -- Politics and government; Exiles -- Political activity; Filibusters; International relations; Cuba; United States; Filibuster -- Seeräuber; Unabhängigkeitsbewegung; Exilschriftsteller; Spanien; USA; Kubaner.; 1800-1899; History